El impacto de la obsolescencia en la propiedad planta y equipo del Hospital Básico Maternidad Babahoyo - Botto Monserrate, Julio Ronny (2020)
This case study is based on the standards that refer to property, plant and equipment, presenting the way in which it is recognized, which must be classified as an asset, taking into account the essential conditions and also presenting its reality. This work is called ´´THE IMPACT OF OBSOLESCENCE ON THE PROPERTY PLANT AND EQUIPMENT OF THE HOSPITAL BASICO MATERNIDAD BABAHOYO´´, which aimed to analyze the accounting procedures applied to the property, plant and equipment of the Hospital Básico Maternidad De Babahoyo, The same that lacks manuals, policies and procedures that regulate the processes of the different departments of the company, causing workers to develop their activities often empirically, these ways of carrying out operations are mostly evidenced in the lack of internal control that you have from fixed assets. For the execution of this investigative work, a mixed methodology was used with a descriptive approach through techniques such as direct observation and interviews directed at administrative staff and operators, with a structured instrument of 10 questions. The most relevant results are directed to the inadequate control of fixed assets, since they are used empirically. The purpose of this research is to contribute to the efficient control of property, plant and equipment, therefore, it was necessary to diagnose the status of production assets and describe the accounting procedures applied to property, plant and equipment of the company.